Cultural Traditions of Hajj and Umrah: A Comparative Study of Madurese Communities in Indonesia and Malaysia - Moh. Hafid Effendy; Erie Hariyanto; Maimun Maimun; Anas Ahmadi; Agus Purnomo Ahmad Putikadyanto (SCAD Independent, 2026)
Local traditions surrounding the Hajj and Umrah pilgrimages among Madurese communities have received limited scholarly attention, particularly within comparative transnational contexts. While existing studies documented the cultural significance of pilgrimage in Madura, less is known about how these traditions are reconfigured when Madurese communities migrate and inhabit different socio-political environments. This study examined how Hajj and Umrah practices are organized, experienced, and transformed among Madurese communities in Indonesia and among Madurese migrants in Malaysia. Employing a qualitative descriptive approach, data were collected through in-depth interviews, participant observation, and documentation involving community members, religious leaders, and academics. The findings revealed a clear contrast between the two contexts: in Madura, pilgrimage traditions remained highly visible and communally celebrated, reinforcing social cohesion and moral recognition, while in Malaysia these practices tended to be simplified and selectively expressed as adaptive responses to minority positioning, sociopolitical regulation, and norms of public visibility. The study demonstrated that Hajj and Umrah function not only as acts of worship but also as culturally embedded performances through which identity, belonging, and social legitimacy are negotiated within transnational social fields. By foregrounding the interplay between ritual, culture, and mobility, this research contributes to broader discussions on lived Islam, migration, and the dynamic transformation of religious practices across national boundaries.